Pendidikan Ramah Anak Studi Kasus SDIT Nur Hidayah Surakarta - Agus Yulianto (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
Child-friendly education model will create students who not only intellectually intelligent but also spiritually intelligent. Unfortunately, theschool has not been a child-friendly environment. Students often experience bully from their friends or abuse from their teachers or another party in school. The objective of this research is to describe the implementation of child-friendly education on students of Class VB SDIT Nur Hidayah Surakarta. This research was conducted by aqualitative descriptive method with a case study approach. The subject of the study were teachers and students of that class. While other teachers, staffs, securities, and headmaster were the informant. Data was collected by observation, interview, and documentation; applying data and method triangulation. Data was analyzed using interactive analysis model. In achild-friendy education environment, students are treated as the object of education but as the subject instead. They are free to learn and to create under conducive environment. Child-friendly education in SDIT Nur Hidayah Surakarta includes: physically friendly, nonphysically-friendly, in-class learning, and out-class learning.Keywords: Education, child-friendlyeducation, child-friendly environment.